Alterations of the fecal and vaginal microbiomes in patients with systemic lupus erythematosus and their associations with immunological profiles - Ling, Zongxin; Cheng, Yiwen; Gao, Jie; Lei, Wenhui; Yan, Xiumei; Hu, Xiaogang; Shao, Li; Liu, Xia; Kang, Runfang (Frontiers in Immunology, 2023)
Background Exploring the human microbiome in multiple body niches is beneficial for clinicians to determine which microbial dysbiosis should be targeted first. We aimed to study whether both the fecal and vaginal microbiomes are disrupted in SLE patients and whether they are correlated, as well as their associations with immunological features. Methods A group of 30 SLE patients and 30 BMI-age-matched healthy controls were recruited. Fecal and vaginal samples were collected, the 16S rRNA gene was sequenced to profile microbiomes, and immunological features were examined. Results Distinct fecal and vaginal bacterial communities and decreased microbial diversity in feces compared with the vagina were found in SLE patients and controls. Altered bacterial communities were found in the feces and vaginas of patients. Compared with the controls, the SLE group had slightly lower gut bacterial diversity, which was accompanied by significantly higher bacterial diversity in their vaginas. The most predominant bacteria differed between feces and the vagina in all groups. Eleven genera differed in patients’ feces; for example, Gardnerella and Lactobacillus increased, whereas Faecalibacterium decreased. Almost all the 13 genera differed in SLE patients’ vaginas, showing higher abundances except for Lactobacillus. Three genera in feces and 11 genera in the vagina were biomarkers for SLE patients. The distinct immunological features were only associated with patients’ vaginal microbiomes; for example, Escherichia−Shigella was negatively associated with serum C4. Conclusions Although SLE patients had fecal and vaginal dysbiosis, dysbiosis in the vagina was more obvious than that in feces. Additionally, only the vaginal microbiome interacted with patients’ immunological features.